Intellectual Capital in Enterprises and a Model Study in an Industrial Zone - Kendirli, Selcuk; Kilic, Sabiha; Cagiran Kendirli, Hulya (Journal of Economic Development, Environment and People, 2014)
Intellectual Capital in Enterprises and a Model Study in an Industrial Zone Abstract The study mainly consists of two parts. The first part includes theoretical knowledge, the second part includes application-oriented information. In the theoretical part of the study, intellectual capital and SMEs are emphasized in general. In the application-oriented part of the study, a field research will be done for Corum SME. In this study, the demographic structure of Corum SMEs, intellectual capital structure and financial performance of this structure will be evaluated. The resulting data will be analyzed in this context. The businesses operating in the Organized Industrial Zone of Corum and those matching the definition of SME will be considered within the research scope. Surveys will be applied by interviewers face to face and each survey will be evaluated individually. After the evaluation, a model will be proposed. The aim of our study is to investigate the relationship between components of intellectual capital in SMEs and business performance. For this reason, a survey will be conducted for SMEs. Since the results of the study will be shared with scientific circles and the public, they will prove to be guiding for Çorum SMEs.